resolva os sistemas abaixo, utilizando a regra de cramer : a ) 3x + y = 7
-x+ 7y=5
b) 2x - y = 3
x + y = 3
c) 3x + y =-4
2x + 5y = 6
Respostas
respondido por:
1
a) 3x+y = 7
-x+7y = 5 *(3)
3x+y = 7
-3x+21y = 15
22y = 22
y = 22/22
y = 1
-x+7y = 5
-x+7(1) = 5
-x+7 = 5
-x = 5-7
-x = -2
x = 2
x = 2 e y = 1.
b) 2x-y = 3
x+y = 3
3x = 6
x = 6/3
x= 2
x+y = 3
2+y = 3
y = 3-2
y = 1
x = 2 e y = 1.
c) 3x+y = -4 *(-5)
2x+5y = 6
-15x-5y = 20
2x+5y = 6
-13x = 26
13x = -26
x = -26/13
x = -2
2x+5y = 6
2(-2) +5y = 6
-4+5y = 6
5y = 6+4
5y = 10
y = 10/5
y = 2
x = -2 e y = 2.
Espero ter ajudado.
-x+7y = 5 *(3)
3x+y = 7
-3x+21y = 15
22y = 22
y = 22/22
y = 1
-x+7y = 5
-x+7(1) = 5
-x+7 = 5
-x = 5-7
-x = -2
x = 2
x = 2 e y = 1.
b) 2x-y = 3
x+y = 3
3x = 6
x = 6/3
x= 2
x+y = 3
2+y = 3
y = 3-2
y = 1
x = 2 e y = 1.
c) 3x+y = -4 *(-5)
2x+5y = 6
-15x-5y = 20
2x+5y = 6
-13x = 26
13x = -26
x = -26/13
x = -2
2x+5y = 6
2(-2) +5y = 6
-4+5y = 6
5y = 6+4
5y = 10
y = 10/5
y = 2
x = -2 e y = 2.
Espero ter ajudado.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás